Atypical miller-fisher syndrome after COVID-19 and sleeve gastrectomy: Contribution of neurochemical markers to early diagnosis - Souheil Zayet; Hajer Zahra; Nabil Belfeki; Timothée Klopfenstein; Beate Hagenkötter (Infectious Medicine, 2022)
Background: The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), began in late 2019. More recently, there have been sporadic case reports on development of Miller-Fisher Syndrome , a rare variant of Guillain-Barré Syndrome in COVID-19 patients. Case report: We reported herein the case of a French young women presenting with ophtalmoplegia, cerebellar ataxia, and universal areflexia following a bariatric surgery (sleeve gastrectomy). A concomitant COVID-19 diagnosis was retained based on microbiological testing. The patient was successfully treated after high-dose intravenous thiamine, but areflexia persisted. Underlying COVID-19 related Miller-Fisher Syndrome was established on physical examination and confirmed by pathologic neurophysiological findings and elevated level of phosphorylated neurofilament heavy chain protein in cerebrospinal fluid analysis. Conclusions: Guillain-Barré Syndrome and its variants after SARS-CoV-2 infection are extremely rare. The measurement of phosphorylated neurofilament heavy chain protein should be considered as an easy tool to detect an early affection of the peripheral nervous system.